The Role of Affections and Emotions in Moralities - Hussein Deeba (حکمت اسرا)
Among man's existential capacities, affections and emotions have a special position in exerting influence on their thoughts and acts. A study of these effects in the domain of ethics, which is one of the most important aspects of personal and social life, will provoke very important discussions. The importance of these discussions will be more appreciated if the kind and rate of influence of affective domain is studied and analyzed in comparison to other competing domains (such as rational domain). The present paper discusses the issue in two domains: the first is an absolutely theoretical domain and a subcategory of meta-ethical issues. The second is in more objective domains of man's moral life, i.e. the domain of moral behaviors and judgments. These studies compare and contrast the domains of meta-ethics and psychology of ethics with Islamic sources. In terms of Islamic sources, the emphasis is put on the expert Ayatollah Jawadi Amuli's works. Accordingly, the discussions are divided into three parts: the first part studies the role of affections in meta-ethical theories and discusses two main meta-ethical approaches. These two approaches are naturalistically descriptive theory and non-descriptive or non-cognitive theory. Having explained the disadvantages of these two theories, this paper elaborates on the relationship between moral values and objective realities. The second part studies the role of affections in moral judgments and discusses the effect of rational domain on moral judgments. Then some views which consider affections and emotions as the only factor influencing moral judgments are explained and criticized. Finally, having accepted the effect of affections on moral judgments, its exclusive causality is rejected. The third part deals with the effect of affections on moral behaviors. It also studies and evaluates emotionalists and cognitivists' views on those grounds that affections and emotions exert influence on moral behavior. Having accepted the strong effect of emotions on moral behavior, the influential role of cognition and intellectual contemplations in moral behavior is also proved.